Bantuan Hukum Timbal Balik Dalam Perampasan Aset Korupsi Antar Lintas Batas Negara - Bisdan Sigalingging (Iuris Studia: Jurnal Kajian Hukum, 2021)
Corruption assets are not only stored in the country, but can also cross borders between countries. Mutual legal assistance in criminal law is an important aspect in eradicating corruption, especially for asset confiscation. This normative research discusses the problem, namely how to tackle corruption in Indonesia through increasing mutual legal assistance cooperation between countries. It was concluded that the 2003 UNCAC Convention and Law Number 1 of 2006 concerning Mutual Legal Aid in Criminal Matters were very effective in overcoming corruption through increasing cooperation in mutual legal assistance, to pursue stolen assets and money that were abroad. Law enforcement officers will easily find out the destination country and the place where money flows or criminal assets are stored. It is hoped that through MLA cooperation, law enforcement officers can easily confiscate assets through NCB Assets Forfeiture or civil forfeiture instruments, including for the transfer of the convicted person, transfer of criminal proceedings, law enforcement cooperation, joint investigations, and special investigation techniques